Relating microtensiometer-based trunk water potential with sap flow, canopy temperature, and trunk and fruit diameter variations for irrigated ‘Honeycrisp’ apple - Blanco, Victor; Kalcsits, Lee (Frontiers in Plant Science, 2024)
Instrumentation plays a key role in modern horticulture. Thus, the microtensiomenter, a new plant-based sensor that continuously monitors trunk water potential (Ψtrunk) can help in irrigation management decisions. To compare the response of the Ψtrunk with other continuous tree water status indicators such as the sap flow rate, the difference between canopy and air temperatures, or the variations of the trunk and fruit diameter, all the sensors were installed in 2022 in a commercial orchard of ‘Honeycrisp’ apple trees with M.9 rootstocks in Washinton State (USA). From the daily evolution of the Ψtrunk, five indicators were considered: predawn, midday, minimum, daily mean, and daily range (the difference between the daily maximum and minimum values). The daily range of Ψtrunk was the most linked to the maximum daily shrinkage (MDS; R2 = 0.42), the canopy-to-air temperature (Tc-Ta; R2 = 0.32), and the sap flow rate (SF; R2 = 0.30). On the other hand, the relative fruit growth rate (FRGR) was more related to the minimum Ψtrunk (R2 = 0.33) and the daily mean Ψtrunk (R2 = 0.32) than to the daily range of Ψtrunk. All indicators derived from Ψtrunk identified changes in tree water status after each irrigation event and had low coefficients of variation and high sensitivity. These results encourage Ψtrunk as a promising candidate for continuous monitoring of tree water status, however, more research is needed to better relate these measures with other widely studied plant-based indicators and identify good combinations of sensors and threshold values.